1998
DOI: 10.1159/000030022
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping of Human Alpha-Fetoprotein

Abstract: Thirty monoclonal antibodies (MoAbs) to human α-fetoprotein (AFP) were compared with one another by two methods: Immunoaffinity electrochromatography or additive ELISA. The first method permitted to analyse the epitopes of native AFP in solution [Abelev et al., Immunol Lett 1994;40:133–138] while the other approach also detects the epitopes of conformationally modified (partly denatured) AFP fixed on the plastic [Yazova et al., Immunol Lett 1990;25:325–330]. Competitive analysis of all MoAbs revealed 10 epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…It is necessary to emphasize that epitopes used in this study belong to different non-crossreacting immunodominant clusters [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to emphasize that epitopes used in this study belong to different non-crossreacting immunodominant clusters [15].…”
Section: Discussionmentioning
confidence: 99%
“…The MoAbs D 10 , F 5 and F 2 , directed to three noncross-reacting epitopes, were used in that work. These MoAbs belong to different epitope clusters [15]: D 10 to AB (N92), F 2 to F (N118) and F 5 to D (N113). The MoAb to macrophage antigen D 11 [16], an unrelated antibody, was introduced in the experiments as a negative control.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yakimenko et al [16] in Dr. Abelev's laboratory confirmed the presence of 6 major epitope clusters and identified several minor epitopes. These results were almost identical to that found by Dr. Nustad et al [17] and Kamakura [18] found that one of the epitopes did apparently contain carbohydrate in their studies.…”
mentioning
confidence: 90%
“…In a recent TD-2 AFP Workshop organized by the International Society for Oncodevelopmental Biology and Medicine (ISOBM), 30 MAbs against AFP were analyzed [8]. Using immunoaffinity electrochromatography and additive ELISA, Abelev's group classified the antibodies into 10 epitopic clusters, I-X, which were divided into 6 antibody groups, A-F [9]. Nustad's group separately classified the panel of MAbs into 5 groups, A-E, by competitive immunoassays [10].…”
Section: Introductionmentioning
confidence: 99%